2012
DOI: 10.1016/j.jweia.2012.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Wind-induced torsional loads on low buildings

Abstract: a b s t r a c tWind-induced instantaneous pressures on low building envelopes continuously vary in temporal and spatial dimensions and this may lead to significant torsional moments on the building's lateral load resisting system. Studies on wind-induced torsional loads on low buildings are very limited. Windinduced torsion provisions in the American Society of Civil Engineers Standard (ASCE/SEI 7-10, 2010), the National Building Code of Canada (NBCC, 2010), and the European Code (EN 1991(EN -1-4, 2005 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Tamura et al (2001) examined the correlation of torsion with along-wind and across-wind forces for rectangular low-rise buildings tested in simulated open and urban terrain exposures. Low-rise buildings of different roof slopes were also tested by Elsharawy et al (2012). Good agreement was found when the results were compared with Isyumov and Case (2000) study for similar tested cases (i.e.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Tamura et al (2001) examined the correlation of torsion with along-wind and across-wind forces for rectangular low-rise buildings tested in simulated open and urban terrain exposures. Low-rise buildings of different roof slopes were also tested by Elsharawy et al (2012). Good agreement was found when the results were compared with Isyumov and Case (2000) study for similar tested cases (i.e.…”
Section: Introductionmentioning
confidence: 88%
“…The power law index α of the mean wind velocity profile was set at α = 0.15. Although the majority of medium height buildings are situated in suburban terrain, an open exposure was considered as higher overall wind loads are expected, as discussed in Elsharawy et al (2012). However, it is also recognized that rougher terrain exposure, in some cases, may result in greater unbalancing of wind loads and torsion.…”
Section: Terrain Simulationsmentioning
confidence: 99%
“…Tamura et al [11] examined correlation of torsion with along-wind and across-wind forces for rectangular low-rise buildings tested in simulated open and urban terrain exposures. Low-rise buildings of different roof slopes were tested by Elsharawy et al [12] but peak torsions evaluated by current wind provisions were found to be different from the measured peak torsion in the wind tunnel.…”
Section: Introductionmentioning
confidence: 98%
“…When these provisions were compared by Elsharawy et al (2012) for three low-rise buildings with different aspect ratios (L/B= 1, 2, 3), significant differences were found in evaluating design wind loads -see Figure 1.…”
Section: Introductionmentioning
confidence: 99%